2022
DOI: 10.1021/acs.inorgchem.1c03719
|View full text |Cite
|
Sign up to set email alerts
|

MnII/III and CeIII/IV Units Supported on an Octahedral Molecular Nanoparticle of CeO2

Abstract: The preparation of three new heterometallic clusters [Ce6Mn12O17(O2CPh)26] (1), [Ce10Mn14O24(O2CPh)32] (2), and [Ce23Mn20O48(OH)2(tbb)46(H2O)4]­(NO3)2 (3; tbb– = 4-tBu-benzoate) is reported. They all possess unprecedented structures with a common feature being the presence of an octahedral CeIV–oxo core: a Ce6 in 1, two edge-fused Ce6 giving a Ce10 bioctahedron in 2, or a larger Ce19 octahedron in 3. Complex 1 is the first Ce6 cluster with a central μ6-O2–. 2 and the cation of 3 are molecular nanoparticles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…[Ce 6 Mn 12 O 17 (O 2 CPh) 26 ] consists of a diamagnetic {Ce 6 O 9 } core with four isostructural, noninteracting {Mn 3 (μ-O 2− ) 2 } (10) units (Figure 13) attached to the surface. 40 Lowtemperature dc and ac susceptibility data reveal that each Mn 3 unit has an S = 2 ground state. Pertinent metric parameters and obtained J MSC are listed in Table 11; the Mn 1 Mn 3 pair is not monoatomically bridged (instead by an η 1 / η 1 -benzoate), so the MSC is not applicable.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…[Ce 6 Mn 12 O 17 (O 2 CPh) 26 ] consists of a diamagnetic {Ce 6 O 9 } core with four isostructural, noninteracting {Mn 3 (μ-O 2− ) 2 } (10) units (Figure 13) attached to the surface. 40 Lowtemperature dc and ac susceptibility data reveal that each Mn 3 unit has an S = 2 ground state. Pertinent metric parameters and obtained J MSC are listed in Table 11; the Mn 1 Mn 3 pair is not monoatomically bridged (instead by an η 1 / η 1 -benzoate), so the MSC is not applicable.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
“…We probe this point with a low-symmetry Mn 3 cluster that is a scalene triangle and thus a 3- J system. [Ce 6 Mn 12 O 17 (O 2 CPh) 26 ] consists of a diamagnetic {Ce 6 O 9 } core with four isostructural, noninteracting {Mn 3 (μ-O 2– ) 2 } ( 10 ) units (Figure ) attached to the surface . Low-temperature dc and ac susceptibility data reveal that each Mn 3 unit has an S = 2 ground state.…”
Section: Results and Discussionmentioning
confidence: 66%
“…For example, Gupta et al characterized [Ce 6 Mn 12 O 17 (O 2 CPh) 26 ], which consisted of four {Mn 3 (μ 3 -O) 2 } surrounding a Ce IV 6 core. 93 Likewise, Thuijs et al reported [Ce 3 Mn 8 O 8 (O 2 CPh) 18 (HO 2 CPh) 2 ] for which the central position in the cluster core was occupied by Ce IV and the surface was composed of two Ce III and eight Mn III sites. 94 Nonetheless, it is important to note that this is not the only arrangement observed.…”
Section: Resultsmentioning
confidence: 99%